Layoffs in a recession and temporary employment subsidies when a recovery is expected - Matthias Göcke (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
Sunk firing costs shelter employment and this effect is typically amplified by uncertainty due to an option value of waiting. Thus, if sunk firing costs are high, e.g. due to a employment protection legislation, and if recession related losses are with a high probability expected to be only transitory and not permanent, a relatively small employment subsidy will be sufficient to avoid layoffs by firms operating with current losses. Depending on the size of sunk hiring costs cyclical layoffs or even permanent job destruction can be avoided by short run subsidies during the beginning of a recession.
Keywords: J63; J68; D81; 330; recession; employment; sunk firing costs; uncertainty; employment subsidy; Kündigung; Kosten; Konjunktur; Beschäftigungseffekt; Arbeitsmarktpolitik; Subvention; Theorie